The Dialogues between Kresna and Arjuna Concerning the Swadarma of a Ksatriya in the Bhagavad Gita of the Ancient Javanese Bhisma Parwa: (Dialog Kresna dan Arjuna tentang Swadharma Ksatriya Episod Bhagavad Gita dalam Bhisma Parwa Jawa Kuno) (Malay Literature, 2016)
The Bhagavad Gita is usually called the fifth veda (pancama veda), together with the four Sanskrit Vedas, namely the Rig Veda, Atharwa Veda, Sama Veda and Yajur Veda. The Balinese are familiar with the five vedas, and know the Bhagavad Gita as the sixth book of the ancient Javanese version of the Mahabharata epic. The Bhagavad Gita that features as a part of the ancient Javanese version of the Bhisma Parwa is ascribed to King Teguh Dharmawangsa Anantavikrama Uttunggadewa of the Kediri Kingdom in the 10th century CE. He is credited to have been responsible for ordering the translation of the Mahabharata (known in Bali as Asta Dasar Parwa-the 18 parwas). This translation effort from Sanskrit into the ancient Javanese language was dubbed mangjawaken Byasamata (translating into Javanese the works of the sage Byasa). The ancient Javanese version of the Bhagavad Gita contains the dialogues between Kresna and Arjuna about the swadarma (holy obligations and responsibilities) of a ksatriya (warrior) according to his wangsa (social class). A ksatriya was deemed responsible for defending his country, fighting against the enemy, as well as for upholding truth, satya wacana (truthfulness), lascarya (sincerity) and sradha bhakti (devotional service).Keywords: Bhagavad Gita, Asta Dasa Parwa, satya wacana, lascarya, bhakti